2007
DOI: 10.1055/s-2007-965146
|View full text |Cite
|
Sign up to set email alerts
|

Is Perioperative Cholangiography Necessary in Children Undergoing Elective Laparoscopic Cholecystectomy?

Abstract: Patients scheduled for elective LC presenting with unremarkable clinical examination, normal liver biochemistry and serum amylase levels, and without dilatation of the biliary tree on ultrasound scan do not need pre- or intra-operative cholangiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…Mattioli et al [17] have reported that the incidence of sub clinical co mmon bile duct stones is low in children. This finding has also been described in a small prospective pediatric study [18].…”
Section: Discussion:-supporting
confidence: 84%
“…Mattioli et al [17] have reported that the incidence of sub clinical co mmon bile duct stones is low in children. This finding has also been described in a small prospective pediatric study [18].…”
Section: Discussion:-supporting
confidence: 84%
“…[1] This finding has also been described in a small prospective pediatric study. [7] In the present series, as there was no evidence of common bile duct stones or altered liver function tests preoperatively in any of the patients, intraoperative cholangiogram was not done. None of the patients had evidence of residual ductal stones during the follow-up period.…”
Section: Discussionmentioning
confidence: 85%
“…[1] This finding has also been described in a small prospective pediatric study. [12] In the present series, as there was no evidence of common bile duct stones or altered liver function tests preoperatively in any of the patients, an intraoperative cholangiogram was not done. None of the patients had any evidence of residual ductal stones during the follow up period.…”
Section: Discussionmentioning
confidence: 88%